Individual- and Organization-Level Work-to-Family Spillover Are Uniquely Associated with Hotel Managers' Work Exhaustion and Satisfaction - Lee, Soomi; Davis, Kelly D.; Neuendorf, Claudia; Grandey, Alicia; Lam, Chun Bun; Almeida, David M. (Frontiers in Psychology, 2016)
Purpose: Building on the Conservation of Resources theory, this paper examined the unique and interactive associations of negative and positive work-to-family spillover (NWFS and PWFS, respectively) at the individual and organizational level with hotel managers’ wok exhaustion and satisfaction, beyond job demands and supervisors’ leadership style. Design/methodology/approach: Guided by the levels of analysis framework, we first tested the unique associations of NWFS and PWFS with emotional exhaustion and job satisfaction at the individual level (571 hotel managers), beyond job demands supervisors’ leadership style. Second, using multilevel modeling, we tested the climate effects of NWFS and PWFS on emotional exhaustion and job satisfaction aggregated at the organizational level (41 hotels). Third, we examined the role of the organizational climate of PWFS in the associations of individual-level NWFS with emotional exhaustion and job satisfaction. Findings: Beyond the effects of psychological job demands and supervisor’s transformational leadership, at the individual level, hotel managers who experienced higher NWFS than other managers reported more exhaustion and lower job satisfaction, whereas those with higher PWFS reported less exhaustion and higher satisfaction. At the organizational level, working in hotels where the average level of NWFS was higher than other hotels was associated with feeling more exhaustion of the individual members; working in hotels with higher PWFS was associated with feeling less exhaustion. The negative link between individual-level NWFS and job satisfaction was buffered when organization-level PWFS was higher, compared to when it was lower. Originality/value: This study moves beyond a focus on traditional job characteristics, toward considering individual and organizational experiences in the work-family interface as unique predictors of work exhaustion and satisfaction. Strengths of the study include illuminating organizational work-family climate effects such that coworkers’ shared experiences of NWFS and PWFS explain individual members’ work exhaustion, beyond their own experiences of spillover. The results also highlight that a high level of organizational PWFS can buffer the negative effects of individual NWFS.